A belief–desire–intention model for blog users' negative emotional norm compliance: Decision-making in crises. Issue 4 (7th August 2017) - Wu, Peng; Shen, Si; He, Daqing; Du, Jia Tina
Abstract : Purpose: The purpose of this paper is to understand blog users' negative emotional norm compliance decision-making in crises (blog users'-NNDC). Design/methodology/approach: A belief–desire–intention (BDI) model to evaluate the blog users'-NNDC (the BDI-NNDC model) was developed. This model was based on three social characteristics: self-interests, expectations and emotions. An experimental study was conducted to evaluate the efficiency of the BDI-NNDC model by using data retrieved from a popular Chinese social network called "Sina Weibo" about three major crises. Findings: The BDI-NNDC model strongly predicted the Blog users'-NNDC. The predictions were as follows: a self-interested blog user posted content that was targeting his own interests; a blogger with high expectations wrote and commented emotionally negative blogs on the condition that the numbers of negative posts increased, while he ignored the norm when there was relatively less negative emotional news; and an emotional blog user obeyed the norm based on the emotional intentions of the blogosphere in most of the cases. Research limitations/implications: The BDI-NNDC model can explain the diffusion of negative emotions by blog users during crises, and this paper shows a way to bridge the social norm modelling and the research of blog users' activity and behaviour characteristics in the context of "real life" crises. However, the criterion for differentiating blog users according to social characteristics needs to be further revised, as the generalizability of the results is limited by the number of cases selected in this study. Practical implications: The current method could be applied to predict emotional trends of blog users who have different social characteristics and it could support government agencies to build strategic responses to crises. Originality/value: This paper supports the creation of normative models and engineering methods to predict blog users'-NNDC and mitigate their effect in real-world crises.